Stable and Broad Spectrum Cross-Protection Against Pepino Mosaic Virus Attained by Mixed Infection - Agüero, Jesús; Gómez-Aix, Cristina; Sempere, Raquel N.; García-Villalba, Julio; García-Núñez, Jorge; Hernando, Yolanda; Aranda, Miguel A. (Frontiers in Plant Science, 2018)
While recent Pepino mosaic virus (PepMV; genus Potexvirus, family Alphaflexiviridae) epidemics seem to be predominantly caused by isolates of the Ch2 genotype, PepMV epidemics in Spain are caused by both Ch2 and EU isolates that co-circulate, representing a challenge in terms of control, including cross-protection. In this work, we hypothesized that mixed infections with two mild isolates of the EU and Ch2 genotypes (PepMV-Sp13 and -PS5, respectively) may be useful in PepMV cross-protection in Spanish epidemics, providing protection against a broad range of aggressive isolates. Thus, we performed a range of field trials and an experimental evolution assay to determine the phenotypic and genetic stability of PepMV-Sp13 and -PS5 mixed infections, as well as their cross-protective efficiency. Our results showed that (i) the phenotype of PepMV-Sp13 and -PS5 mixed infections was mild and did not change significantly when infecting different tomato cultivars or under different environmental conditions, (ii) PepMV-Sp13 and -PS5 mixed infections provided more efficient protection against aggressive EU and Ch2 isolates than single infections, and (iii) PepMV-Sp13 and -PS5, either in single or in mixed infections, were at least as genetically stable as other PepMV isolates occurring naturally in PepMV epidemics.